Effects of tetrandrine on ovum transport in rabbit oviduct - Li Yong-Qing; Xu Yuan-Xiu (Acta Pharmacologica Sinica, 2016)
On isolated oviductal isthmus of rabbits, tetrandrine (1-3 μmol/L) inhibited the spontaneous contraction and the contraction caused by phenylephrine. The pD’2 values of tetrandrine, measured on the oviduct of the rabbits pretreated with estradiol or megestrol, were 4.19 and 4.74, respectively. Tetrandrine 5 mg/kg iv suppressed the increasing intraluminal pressure in situ induced by phenylephrine (0.2 μg/kg). At 48 h after ovulation, tetrandrine delayed the ovum transport through the oviduct and suppressed the activity of ova accelerated by estradiol cyclopentylpropionate (25 μg).